Transcriptomic analyses suggest that mucopolysaccharidosis patients may be less susceptible to COVID‐19. Issue 20 (6th September 2020) - Pierzynowska, Karolina; Gaffke, Lidia; Węgrzyn, Grzegorz
Abstract : We used transcriptomic (RNA‐seq) analyses to determine whether patients suffering from all types and subtypes of mucopolysaccharidosis (MPS), a severe inherited metabolic disease, may be more susceptible to coronavirus disease 2019 (COVID‐19). The expression levels of genes encoding proteins potentially involved in SARS‐CoV‐2 development were estimated in MPS cell lines. Four genes ( GTF2F2, RAB18, TMEM97, PDE4DIP ) coding for proteins potentially facilitating virus development were down‐regulated, while two genes ( FBN1, MFGE8 ), the products of which potentially interfere with virus propagation, were up‐regulated in most MPS types. Although narrowing of respiratory tract and occurrence of thick mucus, characteristic of MPS, are risk factors for COVID‐19, transcriptomic analyses suggest that MPS cells might be less, rather than more, susceptible to SARS‐CoV‐2 infection. Abstract :